Zakat dalam Mazhab Shafi’i: analisis kaedah istinbat hukum = Zakat In Mazhab Shafi’i: method analysis “Istinbat hukum” - Mohamed Shaarani, Ahmad Zakirullah; Ahmad, Ridzwan; Mohd. Noor, Azman; Mohammad, Fidlizan (Lembaga Zakat Negeri Kedah, 2020)
Zakat adalah salah satu dari rukun Islam terpenting terutama yang berkaitan dengan Muamalat, dengan tujuan untuk menyucikan hati dan harta. Dalam membincangkan hukumhukum berkaitan zakat, banyak isu-isu berkaitan zakat yang timbul yang memerlukan kefahaman mendalam berkaitan tentang metodologi hukum Syariah dalam mengeluarkan hukum yang tuntas. Melihat kepada keadaan semasa, nampak seolah bahawa penekanan utama dalam soal zakat ialah jumlah kutipan, disamping beberapa silap faham lain dalam beberapa prinsip hukum berkaitan zakat, tanpa mendalami metodologi hukum sepertimana yang dibincangkan oleh mazhab Shafi‘i dan tanpa mengambil kira objektif utama/maqasid zakat. Menggunakan kajian kepustakaan sepenuhnya, kajian mendapati bahawa mazhabShafie mempunyai beberapa perbezaan dan keistimewaan dalam bidang zakat, seperti adanya konsep khultah yang dijuarai oleh ulama mazhab Shafi‘i dan konsep ini menjadi asas pengiraan bagi zakat perniagaan semasa bagi syarikat-syarikat dan perkongsian, begitu juga zakat sangat mengambil kira kesempurnaan syarat bagi harta berbanding kesempurnaan syarat wajib zakat ke atas individu, dan beberapa prinsip hukum lain yang berkaitan zakat yang menunjukkan keistimewaan metodologi hukum dalam mazhab ini dalam bidang zakat. ********************************************************************************* Zakat is one of the most important pillars of Islam, specifically pertaining to Muamalat, with the purpose of purifying heart and property. In discussing laws related to zakat, many current issues pertaining to zakat arise which require a thorough understanding of the Shariah rules in deriving the accurate laws. Looking at the current situation, it seems that the main concern in the zakat is the amount of collection, as well as other misunderstanding in some of the principle of zakat without properly adhering to the methodology of law deliberated by the Shafi‘i`s madhhab and without considering the real purpose (Maqasid) of zakat. Using the full library study, the findings show that the Shafi‘i madhhab has some distinction and specialty in the zakat fields, such as the concept of khultah which is spearheaded by Shafi‘i scholars and this concept has become the basis of the calculation of current business zakat for companies and partnership, as well as zakat is really much concern on the fulfilment of the asset`s requirement rather that the fulfilment of Zakat is one of the most important pillars of Islam, specifically pertaining to Muamalat, with the purpose of purifying heart and property. In discussing laws related to zakat, many current issues pertaining to zakat arise which require a thorough understanding of the Shariah rules in deriving the accurate laws. Looking at the current situation, it seems that the main concern in the zakat is the amount of collection, as well as other misunderstanding in some of the principle of zakat without properly adhering to the methodology of law deliberated by the Shafi‘i`s madhhab and without considering the real purpose (Maqasid) of zakat. Using the full library study, the findings show that the Shafi‘i madhhab has some distinction and specialty in the zakat fields, such as the concept of khultah which is spearheaded by Shafi‘i scholars and this concept has become the basis of the calculation of current business zakat for companies and partnership, as well as zakat is really much concern on the fulfilment of the asset`s requirement rather that the fulfilment of Zakat is one of the most important pillars of Islam, specifically pertaining to Muamalat, with the purpose of purifying heart and property. In discussing laws related to zakat, many current issues pertaining to zakat arise which require a thorough understanding of the Shariah rules in deriving the accurate laws. Looking at the current situation, it seems that the main concern in the zakat is the amount of collection, as well as other misunderstanding in some of the principle of zakat without properly adhering to the methodology of law deliberated by the Shafi‘i`s madhhab and without considering the real purpose (Maqasid) of zakat. Using the full library study, the findings show that the Shafi‘i madhhab has some distinction and specialty in the zakat fields, such as the concept of khultah which is spearheaded by Shafi‘i scholars and this concept has become the basis of the calculation of current business zakat for companies and partnership, as well as zakat is really much concern on the fulfilment of someone`s taklif/obligation requirement, and other principles related to zakat that underline the specialty of the rule of Law of the madhhab in the field of zakat.